الأخلاق في ضوء القرآن والسّنة ومدى تطبيقها في منهج التّربية الأخلاقية للحلقة الثانية في مدارس دولة الإمارات العربية المتحدة : دراسة استقرائية تحليلية - خييلي، حمامه سعيد محمد سبت (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This research aims to demonstrate the importance of moral education in the light of the Holy Quran and the Sunnah and the ethical education curriculum of the second cycle secondary schools in UAE by explaining the relationship between them. This research follows the inductive and analytical method, inductive by tracing and gathering the information and ideas contained in the Quranic verses and Sunnah and the methodology on the types of ethics, their examples and how to apply them, by analyzing the verses of the Noble Prophets and the Prophetic Hadiths related to moral education, and urging them to analyze the moral education curriculum to learn how to teach ethics, what its objectives, methods, approaches and means, and highlights the importance of this study in being the first study dealt with the moral education of students of the second cycle in the curricula of the United Arab Emirates in the light of Quran and Sunnah. It is expected that this research benefits many groups, such as educational institutions, teachers and teachers of Islamic culture in universities. The importance of the research is also reflected in the need of the Islamic nation in general and the Emirati people in particular to give their people and youth special education. The results obtained by the researcher show that the texts of the Holy Book and the Sunnah is full of examples and evidences that calls for the need to be good ethics, and that the Quran, Sunnah. The curriculum of the UAE has wise leadership, pioneering work and vision for the benefit of its people. It is a leadership aspiring to distinguish its people in all fields of life, and it will be only with moral excellence, and this was recognized by this leadership, and worked to provide the initiative to include moral education in the curriculum.